Description of clean and healthy behavior in prevention of Covid – 19 at students of science University Cut Nyak Dhien in 2022 - Ajmain Ajmain; Kamariyah Kamariyah; Fauziah Fauziah (Institute of Computer Science (IOCS), 2022)
Most of the transmission of COVID - 19 occurs through the touch of hands due to the lack of people in implementing clean and healthy living behaviors (PHBS) as the cause of the rapid spread of the virus. PHBS is a form of embodiment of a healthy life orientation in individual, family and community culture, which aims to improve, maintain and protect their health both physically, mentally, spiritually and socially. The research aims to describe the behavior of students in Science University of Cut Nyak Dhien regarding PHBS in preventing COVID-19. This type of research is a descriptive survey research. The sample in this study was students in Science University of Cut Nyak Dhien is total sampling with 75 respondents. The data were processed and analyzed in a univariate manner. The results showed that the majority of respondents had sufficient knowledge about PHBS, amounting to 45 (60.0%), and a minority of respondents who had less knowledge, numbering 10 (13.3%), negative attitudes about PHBS, amounting to 39 (52.0%). , and a small proportion of positive attitudes amounted to 36 (48.0%), unskilled about PHBS 70 (93.3%), and a minority of skilled respondents amounted to 5 (6.7%). Clean and Healthy Living Behavior according to the Health Protocol really helps to prevent the transmission of COVID-19, higher education plays an important role in providing information and awareness for students to apply PHBS in lifestyle.